Rheological characterisation and prediction of pumpability of strain-hardening cement-based-composites (SHCC) with and without addition of superabsorbent polymers (SAP) at various temperatures. (1st June 2016) - Secrieru, Egor; Mechtcherine, Viktor; Schröfl, Christof; Borin, Dmitry
Highlights: Rheology, tribology and pumpability of fresh SHCC are described. Combined effect of SAP addition and temperature on rheology of SHCC is investigated. Plug flow of SHCC and lubrication layer formation in the pipe are discussed. Correlation between the results obtained by different testing methods is presented. Pumpability prediction of SHCC by means of tribology is validated. Abstract: The paper at hand presents the results of an investigation into the rheological behaviour of strain-hardening cement-based composites (SHCC) with and without the addition of fresh superabsorbent polymers. The effect of temperature variation in the range between 10 and 30 °C is examined in terms of rheology, tribology and pumpability for up to 60 min after mixing. The flow behaviour of SHCC is approximated as that of a Bingham fluid. Furthermore, two methods of estimating mixture pumpability, a tribometer and a Sliding Pipe Rheometer (SLIPER), are applied. The results describe the development of the Bingham parameters and slippage resistance as parameters related to pumpability. Additionally the correlation between the rheological properties and the pumpability of SHCC at various temperatures and times after mixing are analysed. Finally, the predictive capacity of the tribometer with respect to the concrete pumpability is validated by measuring the discharge pressure with SLIPER.